The effectiveness of aromatherapy in the management of labor pain: A meta-analysis - Atike Kaya; Havva Yeşildere Sağlam; Engin Karadağ; Elif Gürsoy (Elsevier, 2023)
One non-pharmacological method that can be used to safely and without negative side effects is aromatherapy. This meta-analysis study was carried out to assess the effectiveness of aromatherapy in the treatment of labor pain. The analysis included 14 randomized controlled trials of aromatherapy interventions for labor pain. In the studies, it was observed that aromatherapy was applied through massage and inhalation using oils such as lavender, jasmine, rose, chamomile, bitter orange, and boswellia. In the meta-analysis, it was discovered that aromatherapy had a beneficial effect on the management of labor pain and reduced labor pain in the intervention group in 11 studies; it was found that there was no effect in 3 studies. According to analysis findings, aromatherapy significantly lessened the intensity of labor pain. The study's findings support the notion that aromatherapy can lessen labor pain.